The Value of Umbilical Cord Blood Bilirubin Measurement in Predicting the Development of Significant Hyperbilirubinemia in Healthy Newborn - Nahar, Zakia; Shahidullah, Md; Mannan, Abdul; Dey, Sanjoy Kumar; Mitra, Ujjal; Selimuzzaman, SM (Bangladesh Journal of Child Health, 2010)
The present study was conducted to investigate the predictability of early serum bilirubin levels on the subsequent development of neonatal hyperbilirubinemia. For this purpose 84 healthy newborn infants were enrolled and followed up for first 5 days of life. Study subjects were divided into two groups. Group-I consisted of 71 subjects, who did not develop significant hyperbilirubinemia (bilirubin <17mg/dl); Group-II consisted of 13 newborns, who developed significant hyperbilirubinemia (bilirubin >17 mg/dl) during the follow up. Of the enrolled subjects, 46 (55%) were male and rest 38 (45%) were female; 64 (76%) were term babies and 20 (24%) were pre-term babies. Significantly higher percentage of pre-term babies developed hyperbilirubinemia. ROC (receiver operating characteristic) analysis demonstrates that the critical value of cord blood bilirubin >2.5mg/dl had the high sensitivity (77%) and specificity (98.6%) to predict the newborn who would develop significant hyperbilirubinemia. At this level the negative predictive value was 96% and positive predictive value 91%. In our setting infants having umbilical cord blood total serum bilirubin (TSB) >2.5 mg/dl should be followed up strictly either in hospital or as an outpatient department on day 5 if practicable. Infants having TSB <2.5mg/dl in cord blood can be discharged early. Key words: Umbilical cord bilirubin; neonatal jaundice; healthy newborn. DOI: 10.3329/bjch.v33i2.5677 Bangladesh Journal of Child Health 2009; Vol.33(2): 50-54